2013
DOI: 10.1038/pr.2013.237
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in asthma control and inflammation in children undergoing adenotonsillectomy

Abstract: Background Observational studies suggest that asthma control improves after adenotonsillectomy, but longitudinal studies that correlate the effect of the procedure on the levels of biomarkers associated with airway inflammation are limited. Methods We conducted a longitudinal, observational study on pediatric patients, both with and without asthma, undergoing adenotonsillectomy. Asthma Control Test (ACT) scores and chitinase activity in the circulation were measured at time of surgery and at 6-month follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 21 publications
(28 reference statements)
2
37
0
Order By: Relevance
“…al demonstrated significant decreases in hospital visits, systemic steroid use and asthma medication use 1‐year after T&A, although these studies did not have control groups. Levin et al also demonstrated improvement in a marker of airway inflammation. Adenotonsillar hypertophy and inflammation may trigger inflammation in the lower airways that improves after T&A. Kheirnadish‐Gozal et al demonstrated significant improvements in acute asthma exacerbations, weekly β‐agonist rescue use and asthma symptom scores in poorly controlled asthmatics 1 year after T&A compared to untreated asthmatics without OSA.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…al demonstrated significant decreases in hospital visits, systemic steroid use and asthma medication use 1‐year after T&A, although these studies did not have control groups. Levin et al also demonstrated improvement in a marker of airway inflammation. Adenotonsillar hypertophy and inflammation may trigger inflammation in the lower airways that improves after T&A. Kheirnadish‐Gozal et al demonstrated significant improvements in acute asthma exacerbations, weekly β‐agonist rescue use and asthma symptom scores in poorly controlled asthmatics 1 year after T&A compared to untreated asthmatics without OSA.…”
Section: Discussionmentioning
confidence: 95%
“…24 Our results are similar to two uncontolled studies. Levin et al 10 demonstrated significant improvement in C-ACT scores six months after T&A with a median increase from 22 to 25 (P < 0.001) and…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations